Socialization of the Program Activities of the Centre for Information and Counseling of High School Adolescents of the City of Palangka Raya - Erawati, Desi (Universitas Tanjungpura, 2024)
Today's youth problems are quite complex with the presence of information technology, where all interactions shift from the real world to the virtual world. One of the problems that teenagers face is the presence of deviant behavior such as student fights, drugs, bullying, free sex cases and more. This article aims to find out how the PIK-R program is in school and how preventive measures are taken. This research uses a qualitative approach, with the primary source being high school students who are actively participating in the PIK-R program in the school. The results of this research show that the program is developed in the form of seminars, workshops, training with the approach of peer tutors or inviting experts/mentors experts in the field of adolescents and children.